ChemInform Abstract: Microwave‐Assisted One‐Pot Synthesis and anti‐Biofilm Activity of 2‐Amino‐1H‐imidazole/triazole Conjugates. Issue 44 (4th November 2014) - Steenackers, Hans; Ermolat'ev, Denis; Trang, Tran Thi Thu; Savalia, Bharat; Sharma, Upendra K.; De Weerdt, Ami; Shah, Anamik; Vanderleyden, Jozef; Van der Eycken, Erik V.
Abstract The synthesized 2‐amino‐1H‐imidazole/triazole conjugates exhibit inhibitory activity against biofilms of S.